A Common Good Approach to Development : Collective Dynamics of Development Processes. - Nebel, Mathias; Garza-Vázquez, Oscar; Sedmak, Clemens (Cambridge, UK : Open Book Publishers, 2022)
This edited collection proposes a common good approach to development theory and practice. Rather than focusing on the outcomes or conditions of development, the contributors concentrate on the quality of development processes, suggesting that a common good dynamic is key in order to trigger development.
Description of the Municipality of Atlixco (State of Puebla, Mexico) -- Interpretation of PGC Dimensions in Atlixco -- Governance Dimension -- Agency Dimension -- Justice Dimension -- Humanity Dimension -- Stability Dimension -- Conclusions: Assessing Our Results -- References -- 12. Assessing the Transformative Impact of Love-Based Microsocial Communities: From Existential Peripheries into the Nexus of the Common Good -- 1. The Transformative Impact of Micro-Social Relationships -- 2. Assessing Microsocial Transformative Experiences: Three Case-Studies -- Casa-Famiglia Rosetta and Community Rehab for Addicted Persons -- II. 'Leaving the Prison before You Get Out': The GRIP Program -- Distance Support for African Schoolchildren: Does 'Feeling' Supported Improve Learning Outcomes? -- 3. Micro-Social Relations: The Incandescent Nucleus of Human Experience and the Nexus of the Common Good -- I. Agency Freedom, and the I-We Dynamism -- II. Justice and Love -- III. Forgiveness: Regenerating Social Bonds -- IV. Stability, Resilience and Care -- V. Humanity and Listing the Goods that Provide the Common Good -- Conclusion -- References -- List of Illustrations -- Chapter 1 -- Chapter 2 -- Chapter 3 -- Chapter 7 -- Chapter 8 -- Chapter 11 -- Chapter 12 -- List of Tables -- Chapter 3 -- Chapter 6 -- Chapter 7 -- Chapter 8 -- Chapter 11 -- Index.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books